Effects of the Close Collaboration with Parents intervention on the quality of family-centered care in NICUs - Toivonen Mirka; Lehtonen Liisa; Ahlqvist-Björkroth Sari; Axelin Anna (United States, 2022)
Background: Systematic training for the neonatal staff to support parents' active involvement is lacking. There is little information about the effectiveness of educational interventions.
Purpose: To evaluate the effects of an educational intervention to neonatal staff on the quality of family-centered care from the perspectives of parents and nurses.
Methods: A quasi-experimental before and after study was carried out in 5 Finnish neonatal units in 2014-2018. Data were collected using the DigiFCC-tools with a 7-point Likert scale. Thirty-one fathers and 53 mothers were recruited before the intervention and 21 fathers and 61 mothers after the intervention. They answered 1 question every evening until their infants' discharge. Each nurse answered 1 corresponding question after every shift, during the same period before and after the intervention. Before the intervention 3239 responses and after the intervention 3092 responses were received from nurses.
Results: The fathers' total score and the score indicating "Shared decision making" were higher after the intervention than before the intervention. The mothers' total score did not differ between the 2 time periods. The nurses' total score was higher after the intervention than before the intervention. Of the individual items, higher scores were found for "Active listening," "Parents' trust in the nurse," and "Emotional support."
Implications for practice: Developing the staff's negotiating and active listening skills facilitates better support for parents during infants' intensive care.
Implications for research: Family-centered care interventions such as Close Collaboration with Parents should be studied in randomized controlled trials, also including child outcomes.